1990
DOI: 10.1017/s0022215100113933
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine fluid replacement in children undergoing tonsillectomy

Abstract: It has been suggested that children undergoing tonsillectomy would benefit from an intravenous infusion, to counteract the period of pre-operative fasting combined with the blood loss at operation. A prospective study of 50 children undergoing tonsillectomy was undertaken. The children were randomly allocated into two groups, one to receive an infusion and a control group. There were no significant differences between the two groups, although the children with an infusion had a longer mean post-operative stay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Antibiotics administered intraoperatively and for 7 days after surgery have decreased pharyngeal pain dramatically and lessened the duration of the pain 11‐13 . Wilson et al 14 found no effect of intravenous hydration on postoperative pain. Concerning nonsteroidal antiinflammatory drugs (NSAIDs), their efficacy in relieving postoperative pain has been well documented, but their mechanism is not definitively known.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Antibiotics administered intraoperatively and for 7 days after surgery have decreased pharyngeal pain dramatically and lessened the duration of the pain 11‐13 . Wilson et al 14 found no effect of intravenous hydration on postoperative pain. Concerning nonsteroidal antiinflammatory drugs (NSAIDs), their efficacy in relieving postoperative pain has been well documented, but their mechanism is not definitively known.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It showed no significant difference in length of stay between enteral and parenteral hydration (mean difference = 9.09, 95% CI [−1.24–19.43], p = 0.08) (Fig. 2 ) but a trend towards a reduction in length of hospital stay in the enteral group [ 23 , 24 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 98%
“…However, it is worth mentioning that there were also children in both study groups who received almost no nutrition except the intravenous fluids during the 24 postoperative hours. Some former studies have shown that there is no role for routine intravenous fluid replacement in children undergoing uncomplicated tonsillectomy because dehydration leads to thirst and drinking (Wilson et al. 1990) However, uncomplicated tonsillectomy does not ensure the child’s proper oral intake after surgery and it seems to be a risk to leave the child without routine intravenous fluid replacement.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need for fluid replacement, and children receiving intravenous fluids also have a longer postoperative stay in hospital. However, it is considered safe to discharge a child before normal oral intake (Wilson et al. 1990, Messner & Barbita 1997, Kearney et al.…”
Section: Introductionmentioning
confidence: 99%